A Coordinated Public Health Laboratory Response to COVID-19 in Mali - Diarra, Bassirou; Kone, Amadou; Guindo, Ibrehima; Bane, Sidy; Doumbia, Lassina; Timbine, Lassana; Diallo, Dramane; Sanogo, Moumine; Togo, Antieme Combo Georges; Coulibaly, Tenin Aminatou; Diallo, Fatimata Amath; Kone, Mahamadou; et al. (Frontiers in Tropical Diseases, 2022)
Ability to rapidly and accurate diagnose pathogens during disease outbreaks is essential for public health. Diagnosis depends largely on laboratory capacity, which can be challenging in resource limited settings. We report Mali’s experience involving four research laboratories in response to the COVID-19 pandemic. This coordinated effort leveraged the emerging infectious pathogens diagnostic capacity and partnerships built from the 2014/2015 Ebola outbreak. Since Mali’s first two COVID-19 cases in March 2020, 349,292 suspected cases were tested in the four Bamako laboratories as of July 31, 2021. Laboratory operation, safety considerations, diagnostic assays, and challenges are described herein from the perspective of a participating laboratory, the Mali University Clinical Research Center (UCRC). We also highlight additional roles of the UCRC laboratory in the COVID-19 response, including roll out of vaccination and research efforts. Mali’s readiness to detect the index cases early in the epidemic and continued response to the COVID-19 pandemic highlight the need for strengthening the critical role and capacity of clinical research laboratories for response to emerging infectious disease epidemics in Africa.